Urgensi Pendidikan Pemakai dalam Menunjang Layanan Informasi di Unit Pelaksana Teknis Perpustakaan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Conzizca, Mika Julia; Rum, Muhammad; Husna, Nailul (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
Introduction. The purpose of this study was to determine the implementation of user education in the Technical Implementation Unit of the Library of the State Islamic University of Sulthan Thaha Saifuddin Jambi, the obstacles faced by user education in supporting information services at the Technical Implementation Unit of the Library of the State Islamic University of Sulthan Thaha Saifuddin Jambi and the efforts made to overcome these obstacles. faced by user education in supporting information services at the Library Technical Implementation Unit of the State Islamic University of Sulthan Thaha Saifuddin Jambi. Research methods. This study uses qualitative research methods, the method of determining the subject is done by purposive sampling. Data analysis. The collection method used in the form of interviews, observations, documentation and data analysis, informants in this study are the Head of the Library, Librarian and Librarian. Results and Discussion. The result of this research is that user education at the Library Technical Implementation Unit of the State Islamic University of Sulthan Thaha Saifuddin Jambi is carried out every year for new students. The material provided during user education is material related to everything about libraries, services and library collections. The methods used in the implementation of user education are lectures, library tours and manuals. The obstacles faced were the lack of awareness and awareness of students about user education, inadequate time and limited facilities and infrastructure, while the efforts made were to motivate new students to take user education, create special classes and improve facilities and infrastructure. Keywords: User education, information services, university library.